THE EVOLUTION OF EMERGING MARKET (EM) SOVEREIGN CDS SPREADS DURING COVID-19 (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The COVID-19 is expected to hit emerging markets particularly hard, as many containment measures havebeen found to be less effective in the context of emerging markets. This study examines emerging marketsovereign CDS spreadsduring the pandemic and assesses the relative importance of global factors, sovereignfundamentals, COVID-19 mortality, and policy responses. The analysis suggests that while emergingmarket sovereign CDS spreads can be explained by regional and global risk factors prior to COVID-19, theywere determined by fiscal space, commodity revenues, and mobility dynamics during the pandemic, but notdirectly by changes in country-specific of the pandemic mortality rates. This case study compares theimportance of dominant market factors relative to COVID-19 dynamics and policy responses to explain thedaily evolution of emerging markets (EM) sovereign CDS spreads in the first half of 2020.